Democracy, race, and justice : the speeches and writings of Sadie T. M. Alexander - Alexander, Sadie Tanner Mossell, 1898-1989 (Yale University Press, 2021)
In 1921, Sadie Tanner Mossell Alexander became the first Black American to gain a Ph. D. degree in economics. Unable to find employment as an economist because of discrimination, Alexander became a lawyer so that she could press for equal rights for African Americans. Although her historical significance has been relatively ignored, Alexander was a pioneering civil rights activist who used both the law and economic analysis to challenge racial inequities and deprivations. This volume - a recovery of Sadie Alexander's economic thought - provides a comprehensive account of her thought-provoking speeches and writings on the relationship between democracy, race, and justice. Nina Banks's introductions bring fresh insight into the events and ideologies that underpinned Alexander's outlook and activism. A brilliant intellectual, Alexander called for bold, redistributive policies that would ensure racial justice for Black Americans while also providing a foundation to safeguard democracy."--